2010
DOI: 10.3989/scimar.2011.75n1061
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual variation of shoot density and biomass, nitrogen and phosphorus content of the leaves, and epiphyte load of the seagrass <i>Posidonia oceanica</i> (L.) Delile off Mallorca, western Mediterranean

Abstract: SUMMARY:The epiphyte load, the ash content of the epiphytes, the leaf biomass, the nitrogen and phosphorus content of the leaves, and the density of shoots of the Mediterranean seagrass Posidonia oceanica (L.) Delile were monitored yearly from 2003 to 2008 in two shallow meadows off Mallorca (western Mediterranean) with the aim of identifying the responses of P. oceanica meadows to mid-term environmental variability. Inter-annual variability of P. oceanica meadows was significant for most of the descriptors ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
(60 reference statements)
0
5
1
Order By: Relevance
“…This result may be contrary to what was expected, since previous studies have shown how the energy of the echo at high frequencies tends to increase with the increasing seagrass biomass [45]. Nevertheless, biomass and shoot density do not necessarily present a positive relationship [50,51], since the number of leaves per shoot varies as well as the leaf length, owing to several factors, such as the season or the occurrence of severe storms. In addition, there are other factors that can contribute to decreasing the level of the echo when the density increases.…”
Section: Acoustic Detection and Characterization Of P Oceanica Meadowscontrasting
confidence: 59%
“…This result may be contrary to what was expected, since previous studies have shown how the energy of the echo at high frequencies tends to increase with the increasing seagrass biomass [45]. Nevertheless, biomass and shoot density do not necessarily present a positive relationship [50,51], since the number of leaves per shoot varies as well as the leaf length, owing to several factors, such as the season or the occurrence of severe storms. In addition, there are other factors that can contribute to decreasing the level of the echo when the density increases.…”
Section: Acoustic Detection and Characterization Of P Oceanica Meadowscontrasting
confidence: 59%
“…). Owing to inter‐annual variations in epiphyte loads (Terrados & Medina Pons ), sampling designs with a number of controls suitable to separate the natural and human‐induced variability of the system are needed (De Biasi et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In shallow meadows, the loss of old P. oceanica leaves occurs in late summer, whereas this occurs later in deep meadows, where it is possible to observe highly colonized old leaves in autumn (Mazzella & Ott ). Inter‐annual variations in epiphyte load have also been observed (Terrados & Medina Pons ). Changes in epiphyte abundance may be related to changes in herbivore pressure or nutrient availability.…”
Section: Temporal Dynamicsmentioning
confidence: 91%
“…obs. Location Latitude Cymodocea nodosa Agostini et al [ 72 ] 12 Urbinu lagoon, Corsica 42.02 Cymodocea nodosa Duarte and Sand-Jensen [ 71 ] 47 Ebro Delta, Spain 40.72 Cymodocea nodosa Sghaier et al [ 75 ] 36 Monastir Bay, Tunisia 35.37 Cymodocea nodosa Peduzzi and Vukovic [ 74 ] 17 Golf of Trieste, Italy 45.7 Cymodocea nodosa Cunha e Duarte [ 73 ] 5 Ria Formosa, Portugal 37.10 Halodule wrightii Hall et al [ 60 ] 12 Florida Bay, USA 25.14 Halodule wrightii Creed (this study) 992 Multiple sites, American continent Posidonia oceanica Terrados and Pons [ 76 ] 5 Magaluf, Mallorca Island, Spain 39.30 Posidonia oceanica Terrados and Pons [ 76 ] 5 Ses Salines, Mallorca Island, Spain 39.15 Posidonia sinuosa Keulen [ 77 ...…”
Section: Methodsmentioning
confidence: 98%